2020
DOI: 10.3389/fmicb.2020.00447
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Fungal Community and Diversity in Doushen With Different Flavors

Abstract: Doushen, a traditional Chinese fermented soybean product, may be spiced or spicy depending on whether pepper powder is added. While numerous studies have investigated the microbial communities of other fermented foods, little is known on the fungal diversity of Doushen. Therefore, in this study, we investigated the fungal community and diversity in both spiced and spicy Doushen. Our results revealed that fungal species richness significantly differed between the samples with different flavors. A total of nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Although there were great differences in microbial community structure in different Douchi samples, the functional expression and fermentation characteristics of the same microorganism in Douchi samples are basically the same (Wang et al, 2012). In this study, Procrustes analysis was used to find that the taste quality and the flora in Douchi samples had the same trend (Luo et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although there were great differences in microbial community structure in different Douchi samples, the functional expression and fermentation characteristics of the same microorganism in Douchi samples are basically the same (Wang et al, 2012). In this study, Procrustes analysis was used to find that the taste quality and the flora in Douchi samples had the same trend (Luo et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…Although there were great differences in microbial community structure in different Douchi samples, the functional expression and fermentation characteristics of the same microorganism in Douchi samples are basically the same (Wang et al., 2012). In this study, Procrustes analysis was used to find that the taste quality and the flora in Douchi samples had the same trend (Luo et al., 2020). At the same time, the results of correlation analysis showed that Debaryomyces and Trichosporon were positively correlated with the intensity of the excellent taste index of Douchi samples, while Cladosporium and Candida were positively correlated with the intensity of the defective taste index.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, TBZ is very widely used on a large number of different types of cultures from potatoes, soya beans, bananas, mangoes, peas and grapes [ 64 ], increasing the risk of field contact between environmental fungi potentially pathogenic to humans and suboptimal or spray drift deposit concentrations, allowing an increase in the MIC of FCZ. This is particularly true for the C gattii species complex, which has already been isolated from mango trees [ 70 ], as well as C. neoformans , which has already been isolated from soybean-derived products [ 71 ]. BMZ is one of the three molecules that generated the highest number of colonies with elevated MIC of FCZ among all the pesticides tested.…”
Section: Discussionmentioning
confidence: 99%
“…Different types of microbes, coexist in traditional foods, have different roles in food production ( Zhang et al, 2018 , 2021 ; Zhu et al, 2018 ; Luo et al, 2020 ). In the present study, we detected various kinds of bacteria in bacon, including nine dominant genera: Staphylococcus , Psychrobacter , Pseudomonas , Acinetobacter , Macrococcus , Brochothrix , Cupriavidus , Massilia , and Carnobacterium .…”
Section: Discussionmentioning
confidence: 99%
“…The SparCC algorithm was applied to investigate the correlation of all bacterial genera. Correlation networks and redundancy analysis (RDA) were made using the Biomarker biocloud tools ( Luo et al, 2020 ; Zhang et al, 2021 ). Data of the physicochemical characterization used for RDA was showed in our previous study ( Zhang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%